2019
DOI: 10.1080/15384101.2019.1646068
|View full text |Cite
|
Sign up to set email alerts
|

The NEDD8-activating enzyme inhibitor MLN4924 induces DNA damage in Ph+ leukemia and sensitizes for ABL kinase inhibitors

Abstract: The BCR-ABL1 fusion gene is the driver oncogene in chronic myeloid leukemia (CML) and Philadelphia-chromosome positive (Ph+) acute lymphoblastic leukemia (ALL). The introduction of tyrosine kinase inhibitors (TKIs) targeting the ABL kinase (such as imatinib) has dramatically improved survival of CML and Ph+ ALL patients. However, primary and acquired resistance to TKIs remains a clinical challenge. Ph+ leukemia patients who achieve a complete cytogenetic (CCR) or deep molecular response (MR) (≥4.5log reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Neddylation is a type of important post-translational modifications (PTM) that mainly modulates protein stability. Accumulating evidences have shown that targeting the neddylation process could be an appealing strategy for anticancer therapy with particular efficacy in hematologic malignancies (Bahjat et al, 2019; Gu et al, 2014; Guo et al, 2019; Leclerc et al, 2016; Liu et al, 2018; Milhollen et al, 2010; Paiva et al, 2015; Soucy et al, 2009; Swords et al, 2018; Yin et al, 2019). On the other hand, neddylation is a specific PTM that modifies multiple Lys residues in BCR-ABL, shielding this oncoprotein to compete ubiquitination-mediated degradation, which provides a reasonable explanation on the poor in vivo efficacy of PROTAC-based degraders for BCR-ABL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neddylation is a type of important post-translational modifications (PTM) that mainly modulates protein stability. Accumulating evidences have shown that targeting the neddylation process could be an appealing strategy for anticancer therapy with particular efficacy in hematologic malignancies (Bahjat et al, 2019; Gu et al, 2014; Guo et al, 2019; Leclerc et al, 2016; Liu et al, 2018; Milhollen et al, 2010; Paiva et al, 2015; Soucy et al, 2009; Swords et al, 2018; Yin et al, 2019). On the other hand, neddylation is a specific PTM that modifies multiple Lys residues in BCR-ABL, shielding this oncoprotein to compete ubiquitination-mediated degradation, which provides a reasonable explanation on the poor in vivo efficacy of PROTAC-based degraders for BCR-ABL.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neddylation is a specific PTM that modifies multiple Lys residues in BCR-ABL, shielding this oncoprotein to compete ubiquitination-mediated degradation, which provides a reasonable explanation on the poor in vivo efficacy of PROTAC-based degraders for BCR-ABL. MLN4924, a NEDD8-activating E1 enzyme inhibitor, has been shown to inhibit the survival of both wild-type (WT) and T315I-BCR-ABL leukemia cells as well as leukemia-initiating cells ( Liu et al, 2018; Bahjat et al, 2019; Guo et al, 2019). Moreover, clinical trials of MLN4924 in combination with anticancer agents in acute myeloid leukemia (AML) have progressed to phase II (NCT03745352 and PEVENAZA [NCT04266795]) and III (PANTHER[NCT03268954] and PEVOLAM[NCT04090736]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of cleaved caspase3 and cleaved caspase7 are increased, and the expression levels of Bcl-2 and Bcl-XL are decreased in a concentration-dependent manner with the treatment of MLN4924 against different cancer cells. Apoptosis induced by pharmaceutical inhibition of NEDDylation suppresses tumor growth in leukemia [ 133 135 ], colorectal cancer [ 136 ], ewing sarcoma [ 137 ], urothelial carcinoma [ 138 ], head and neck squamous cell carcinoma and intrahepatic cholangiocarcinoma [ 128 , 139 ]. MLN4924-induced apoptosis includes enhancing the accumulation of CDT1 [ 140 ], inducing the dramatic accumulation of CRL E3 substrate I-kappa-B-alpha (IKB-α) [ 141 ] and increasing the expression of NOXA [ 142 ].…”
Section: Pharmacological Mechanisms Of Mln4924 In Cancersmentioning
confidence: 99%
“…Since the SCF complex is also implicated in the regulation of ATF4 ubiquitination and degradation [104], limiting SCF activity via NEDD8 inhibitors may limit leukemia progression. Along these lines, NEDD8 inhibitors sensitize ALL and CML cells to ABL kinase inhibitors [105].…”
Section: Exaggerating Er Stress To Trigger Upr-mediated Apoptosismentioning
confidence: 99%